2016
DOI: 10.1016/j.wasman.2015.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Marine litter on Mediterranean shores: Analysis of composition, spatial distribution and sources in north-western Adriatic beaches

Abstract: Marine litter is one descriptor in the EU Marine Strategy Framework Directive (MSFD). This study provides the first account of an MSFD indicator (Trends in the amount of litter deposited on coastlines) for the north-western Adriatic. Five beaches were sampled in 2015. Plastic dominated in terms of abundance, followed by paper and other groups. The average density was 0.2 litter items m(-2), but at one beach it raised to 0.57 items m(-2). The major categories were cigarette butts, unrecognizable plastic pieces,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
91
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(109 citation statements)
references
References 36 publications
13
91
1
4
Order By: Relevance
“…Plastic litter has been reported from northern Adriatic beaches (Laglbauer et al, 2014;Munari et al, 2016), coastal sediments (Vianello et al, 2013;Blašković et al, 2017), surface waters (Suaria and Aliani, 2014;Gajšt et al, 2016;Suaria et al, 2016) and in very large amounts on the seafloor (Galgani et al, 2000;Strafella et al, 2015;Pasquini et al, 2016), where litter densities are among the highest of the entire Mediterranean basin. Ingestion of plastic by Adriatic fauna has been reported for marine turtles (Lazar and Gračan, 2011;Poppi et al, 2012), sperm whales (Mazzariol et al, 2011) and dolphins (Pribanic et al, 1999) as well as from commercial fish (Avio et al, 2015) and crustacean species (Wieczorek et al, 1999).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Plastic litter has been reported from northern Adriatic beaches (Laglbauer et al, 2014;Munari et al, 2016), coastal sediments (Vianello et al, 2013;Blašković et al, 2017), surface waters (Suaria and Aliani, 2014;Gajšt et al, 2016;Suaria et al, 2016) and in very large amounts on the seafloor (Galgani et al, 2000;Strafella et al, 2015;Pasquini et al, 2016), where litter densities are among the highest of the entire Mediterranean basin. Ingestion of plastic by Adriatic fauna has been reported for marine turtles (Lazar and Gračan, 2011;Poppi et al, 2012), sperm whales (Mazzariol et al, 2011) and dolphins (Pribanic et al, 1999) as well as from commercial fish (Avio et al, 2015) and crustacean species (Wieczorek et al, 1999).…”
Section: Study Areamentioning
confidence: 99%
“…Furthermore, even relatively highresolution regional models, like the one employed here, cannot resolve complex shoreline topography. Additionally, a resource manager coordinating cleanup efforts is not faced with the mean state, which is most commonly reported by modeling studies, but instead must respond to debris loads that can vary in space and time (Kako et al, 2010(Kako et al, , 2011 in response to numerous environmental (Critchell and Lambrechts, 2016) and human factors (Slavin et al, 2012;Munari et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This is especially well-known in the Mediterranean Sea which is a semienclosed sea with a very slow flush rate; large populations live along its coasts and environmental awareness among many of these inhabitants is not particularly high (Laubier, 2005). Efforts to address the acute problems of beach litter by the 22 countries on the Mediterranean seashores are beginning to take shape, albeit slowly (Alkalay et al, 2007;Laglbauer et al, 2014;Poeta et al, 2014;Munari et al, 2016;Poeta et al, 2016;Pasternak et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While several studies have conducted surveys and identified a variety of activities generating marine litter (e.g., Slavin et al, 2012;, Alkalay et al, 2007;Poeta et al, 2014;Munari et al, 2016) the novelty of this paper is its surveying of litter found on a coastal area within a single town over time and space. Although all three of the spaces surveyed are beaches, different activities take place in each.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation